Efeitos do uso associado da cocaína e clonazepam no comportamento tipo ansioso, sono e neurogênese em ratos - Dokkedal Silva, Vinicius [UNIFESP] (2019)
Introduction: The recreational use of psychotropic substances is a growing problem in the Brazilian society and around the world. Recently, the use of clonazepam to ameliorate side-effects from cocaine use has been reported. Objectives: To evaluate the effects of the combination of cocaine and clonazepam in the anxiety-like behavior, sleep and neurogenesis in rats. Methods: In experiment 1, animals were treated for 16 days with different doses of cocaine and clonazepam and had their behavior evaluated in open field and elevated plus-maze tests before and after the treatment phase. In experiment 2, animals were treated for 16 days with cocaine, clonazepam or both drugs, receiving doses based in the results from experiment 1. The acute effects on sleep were evaluated during the first day of treatment. At the end of the treatment phase, animals underwent tests for evaluation of anxiety-like behavior. After these procedures, rats were subjected to transcardial perfusion and their brains were collected for analysis of neurogenesis in the dentate gyrus of the hippocampus. Results: In experiment 1, the doses which elicited the appearance of more pronounced anxiety-like behaviors were 1.25 mg/kg of clonazepam and 15 mg/kg of cocaine. In experiment 2, the behavioral tests found alterations in locomotor and exploratory activities, indicating the emergence of withdrawal syndrome and consequently, anxiety-like behavior. Animals treated with both cocaine and clonazepam presented, in acute sleep recording, reduction of REM sleep during the light phase and increase in REM sleep onset latency, indicating alterations in sleep architecture, which was also observed in the group treated solely with cocaine. The group treated solely with clonazepam did not present significant differences regarding these parameters. Neurogenesis analyses did not find significant results. It is possible that other factors participate in the pathways by which cocaine and clonazepam affect this process and modulate the effects that both substances can have in neurogenesis. Conclusions: The results from this study show that the interaction between cocaine and clonazepam can have negative effects on different aspects of the organism in an animal model, justifying more in-depth studies about this interaction.